Evaluation of Rubber band ligation technique for Internal Haemorrhoids - Saxena, Anand; K Parate, Smita (International Journal of Medical Research and Review, 2014)
Introduction: Hemorrhoids are masses or clumps or “cushions” of tissues consisting of muscle and elastic fibres with enlarged, bulging blood vessels and surrounding supporting tissues present in the anal canal of an individual suffering from the disease. It is one of the common reasons for surgical OPD visit. In this study we tried to find out effectiveness of Ring band ligation technique 1st degree, 2nd degree & some of the 3rd degree hemorrhoids. Methods: All the patients coming to surgical OPD of tertiary care teaching hospital from June 2012 to December 2013 and diagnosed as a case of Hemorrhoids were included in study. Proctoscopic examination found to have first-, second-, and non-bulky, non edematous third-degree haemorrhoids were included for band ligation. Results: Out of total patients 202 were males and 145 were females. Bleeding per rectum (52%), discomfort during defecation (58%) and constipation (47%) were most common symptoms. Most common post-ligation/residual symptoms were bleeding (32 %), pain & discomfort (29.4 %) & constipation (21 %).70 % of patients are cured and 14 % have shown significant improvement. Conclusion: Rubber band ligation as first line treatment for 2nd degree lesion, however for 3rd degree lesion Open hemorrhoidectomy is always better.